Surgical emergencies in pregnancy in the era of modern diagnostics and treatment - Ramanuj Mukherjee; Sudipta Samanta (Elsevier, 2019)
Pregnancy can be complicated with different surgical emergencies which may potentially endanger the mother as well as foetus. In the modern era of advanced diagnostics and treatments, neither of them in response to a surgical emergency in a pregnant woman should be delayed. Appropriate early intervention is essential to decrease the morbidity and mortality. Following article encompasses common surgical emergencies that can arise in a pregnant woman and tries to suggest the approach that may be taken to reduce the burden of morbidity and mortality. Keywords: Appendicitis, Ectopic pregnancy, Pregnancy, Surgical emergency